1981
DOI: 10.1038/sc.1981.25
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia as a sequela to dorsal disc prolapse

Abstract: Abstract. A retrospective study of seven patients referred to a spinal injury unit following surger y for thoracic disc prolapse is presented. Early diagnosis and increased awareness of the condition followed by lateral rhachotomy or anterolateral decompression is essential if the former dismal prognosis is to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
(42 reference statements)
0
3
1
Order By: Relevance
“…Previous studies have demonstrated inconsistencies in whether the anterior or posterolateral approach is associated with a greater rate of complications, including paraplegia and death (1,(13)(14)(15). However, our study did not find significantly different rates of perioperative complications including death, urinary tract infection, pneumonia, sepsis, bleeding transfusions, unplanned intubation, readmission, reoperation within the general or matched cohort.…”
Section: Perioperative Complicationscontrasting
confidence: 78%
See 1 more Smart Citation
“…Previous studies have demonstrated inconsistencies in whether the anterior or posterolateral approach is associated with a greater rate of complications, including paraplegia and death (1,(13)(14)(15). However, our study did not find significantly different rates of perioperative complications including death, urinary tract infection, pneumonia, sepsis, bleeding transfusions, unplanned intubation, readmission, reoperation within the general or matched cohort.…”
Section: Perioperative Complicationscontrasting
confidence: 78%
“…Finally, the NSQIP does not include all complications that could be of interest in TDH repairs; it does not provide data on neurologic degeneration following surgery (e.g., paraplegia, hemiplegia), while past studies have documented neurologic degeneration as a complication of both approaches (Table 3) (1,4,8,(13)(14)(15). This is a large limitation, as reported rates of neurologic deficits following surgery range from 1.3-4% in anterior approaches and from 0.9-28.6% in posterolateral approaches in reviews and case series (1,4,8,(13)(14)(15). Rarer neurological outcomes reported in case reports of anterior approaches include abducens nerve palsy and intercostal nerve pain (17,18).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The flexibility granted by this procedure allows it to be used for the treatment of several spinal disorders including abnormalities of thoracic discs, tumors (primary and metastatic), infection, trauma, and deformity. 2,3,5,[7][8][9]13,15,[17][18][19][20][21][22] Despite these advantages, there are several drawbacks to this procedure. 5,9,13,19 The degree of difficulty posed by the operation requires experience, expertise, and a working knowledge of thoracic and retroperitoneal anatomical structures.…”
Section: The Lateral Extracavitary Approachmentioning
confidence: 99%
“…The risk of performing surgery at the wrong spinal level is ever present and obliges the surgeon to be vigilant and definitive in identifying the appropriate surgical level. 2,35 As stated earlier, the treatment of herniated thoracic discs has undergone significant changes since the first surgeries were attempted. Early cases were treated solely via a dorsal approach and involved a significant risk of causing irreversible paraplegia, 12,13 with operative mortalities approaching 10%.…”
mentioning
confidence: 99%